Educations in ethnic violence identity, educational bubbles, and resource mobilization - Lange, Matthew (Cambridge University Press, 2011)
"In Educations in Ethnic Violence, Matthew Lange explores the effects education has on ethnic violence. Lange contradicts the widely held belief that education promotes peace and tolerance. Rather, Lange finds that education commonly contributes to aggression, especially in environments with ethnic divisions, limited resources and ineffective political institutions. He describes four ways in which organized learning spurs ethnic conflicts. Socialization in school shapes students' identities and the norms governing intercommunal relations. Education can also increase students' frustration and aggression when their expectations are not met. Sometimes, the competitive atmosphere gives students an incentive to participate in violence. Finally, education provides students with superior abilities to mobilize violent ethnic movements. Lange employs a cross-national statistical analysis with case studies of Sri Lanka, Cyprus, the Palestinian territories, India, sub-Saharan Africa, Canada and Germany"-- Provided by publisher